Isolation and characterization of homogeneous heat-labile enterotoxins with high specific activity from Escherichia coli cultures. - Clements, J D (1979)
The heat-labile enterotoxin (LT) has been isolated in homogeneous form with high specific activity from three sources: cell-free supernatant, NaCl extract, and whole-cell lysates of an enterotoxigenic Escherichia coli strain. In vitro immunological assays were used in lieu of tedious and highly variable bioassays to recognize fractions with activity. This revealed that the major portion of the LT remained adherent to columns containing agarose, from which it could be eluted quantitatively in practically homogeneous form by galactose. Isolated LT has remarkable similarities to the cholera enterotoxin (choleragen) in both subunit structure and amino acid composition, although there are also notable differences in these two enterotoxins, which are related immunologically and by mode of action. Unlike choleragen, in which the A region is totally nicked, E. coli LT, depending on its source, is activated by proteolytic processing. The activity of LT is equivalent to that of choleragen in bioassays on adrenal cells, in rabbit skin, and in rabbit ileal loops, especially when, depending on the source of material, the LT has been activated by treatment with trypsin. The whole-cell lysate is the richest source of LT.